Bioinformatics insights into TMPO-AS1–let-7b-5p–ESPL1/E2F8 regulatory axis in breast cancer - Nema, Rajeev; Vats, Prerna; Singh, Aditi; Thilakan, Jaya; Brahmachari, Swagata; Kulkarni, Pallavi; Baweja, Bhavika; Saini, Chainsee; Goel, Sudhir K.; Arya, Neha; Kumar, Ashok (Frontiers in Cell and Developmental Biology, 2025)
BackgroundBreast cancer (BC) is the most frequently diagnosed malignancy in women, contributing to high morbidity and mortality rates. Dysregulation of Extra Spindle Pole Bodies Like 1 (ESPL1), a mitotic regulator essential for chromosomal segregation, is frequently upregulated in cancers. However, the mechanisms underlying ESPL1 overexpression and its prognostic relevance in BC remain unclear.MethodsThe study performed the data mining of The Cancer Genome Atlas (TCGA) using various web-based computational tools, including TIMER 2.0, UALCAN, FIREHOSE, TISIDB, GEPIA2, OncoDB, TCGA Portal, TCGAnalyzeR v1.0, bc-GenExMiner v5.0, TNMplot, and DriverDBv4 to compare ESPL1 expression in tumor vs. normal tissues across pan-cancer and BC subtypes. The Kaplan-Meier (KM) Plotter database was used to determine the association between ESPL1 expression and the survival outcomes of BC patients. miRNet, TACCO, and CancerMIRNome databases were used to analyze miRNAs correlated with ESPL1, while lncRNAs were analyzed using the Enrichr database. For experimental validation, ESPL1 expression level was analyzed in BC tumor and adjacent normal tissue collected from BC patients.ResultsWe found that ESPL1 gene was significantly overexpressed in tumors, metastatic tissues, and circulating tumor cells, with tumor samples showing an overall 4-fold increase in expression compared to adjacent normal tissue of BC patients. Furthermore, BC patients with high ESPL1 expression exhibited shorter overall survival (OS), disease-free survival (DFS), and relapse-free survival (RFS) compared to patients with low expression. Tumors from ER-negative and PR-negative BC patients exhibited elevated expression levels of both ESPL1 and the transcription factor E2F8. Moreover, increased levels of ESPL1 and E2F8 were positively correlated with lncRNA TMPO-AS1, while negatively correlated with hsa-let-7b-5p. Notably, the 3′ untranslated region (3′UTR) of ESPL1 showed strong binding sites for hsa-let-7b-5p. We also identified Hesperidin as a high affinity ESPL1 binders, suggesting novel therapeutic candidates targeting this oncogenic network.